ORGANIZATIONAL AND ECONOMIC PRINCIPLES OF OPTIMIZING THE FINANCIAL AND ECONOMIC ACTIVITY OF HEALTHCARE INSTITUTIONS UNDER CONDITIONS OF REFORM - Zaza, Ilyas (Public Management and Policy, 2025)
The article identifies the organizational and economic principles of optimization of financial and economic activities of health care institutions in the context of reform as a basis for increasing the efficiency of resource management. It is revealed that the formation of state policy in the field of health care is based on legislative provisions on the definition of strategic goals, priorities and regulatory framework of financing. It is stated that budget financing is carried out through state and local budgets, as well as other sources, which ensures transparency in the allocation of resources and increases the efficiency of the use of funds. It is emphasized that the introduction of the status of non-profit enterprises contributes to the financial autonomy of institutions, allowing them to independently determine the directions of resource use and conclude contracts. The importance of digital transformation of management processes, in particular through the eHealth platform, which provides monitoring of costs and the effectiveness of the use of financial resources, is emphasized. It was stated that the program of medical guarantees establishes state obligations to fully pay for medical services and medicines, forming a stable financial environment for medical institutions. It is determined that the diversification of funding sources allows to increase the resilience of institutions to economic fluctuations and contributes to the introduction of innovative management methods. It is noted that effective management of financial flows requires a single control mechanism, a system for monitoring costs and evaluating performance.